IIUM students count: an evaluation of remote teaching and learning practice during covid-19 - Mohd. Ali, Noor Saadiah; Saidin, Nurhafizah; Md Nor, Nurur Raudzah; Aling, Noor Asiah; Ismail, Nur Farrah Syazwanie; Fauzi, Muhammad Ashraf (Centre of Foundation Studies, International Islamic University Malaysia, 2021)
The world spread of infectious disease Covid-19 has posed challenges to many institutions that have mandated the institution to move to remote teaching and learning (RTL) - a temporary access to instructional delivery as an alternative delivery mode during the pandemic crisis. This present study aimed to have an overview of the effectiveness and readiness of pre-university students of International Islamic University Malaysia (IIUM) during the pandemic of Covid-19. Data on students’ demographic, expectation, platform availability, satisfaction and readiness were collected and analyzed which involved 515 respondents. Here, we provide a concise report based on a model that is validated by means of partial least square (PLS) through structural equation modelling (SEM) and descriptive analysis. Outcomes of the findings revealed important implication for the optimization and improvement of remote learning and knowledge acquisitions method for the preparation of long-term Covid-19 pandemic. Furthermore, these findings can be the foundation for further investigations on how to improvise the RTL for better implementation in developing humankind and the society that is coherent with the Sustainable Development Goal (SDG-4).